SETTLEMENT OF LAND DISPUTES THROUGH MEDIATION - Tetty Marlina Tarigan (Proceeding International Seminar of Islamic Studies, 2021)
In essence, a land case constitutes a conflict of interest in the land sector between one party and another, as a concrete example between an individual and an individual, an individual with a legal entity, a legal entity with a legal entity and so on. For legal certainty mandated by the main agrarian law, settlement of land dispute cases, among others, to provide response/reaction/settlement to interested parties (community dan government). In addition, it provides equal treatment to the parties and the opportunity in a transparent manner to present their opinion on the issue. In certain cases, they may be given the freedom to determine their own dispute settlement formulas.Keywords: Settlement, Dispute, Land, Mediation.